The Effect of Auditory Perception Training on Speech Ability and Hearing Impairment in Children - Sudarman, Sudarman; Mangunsong, Roy Romey Daulas (Poltekkes Kemenkes Surakarta, 2024)
Background: Hearing is one of the five senses that plays an important role in early childhood development. With hearing, a child can learn to speak, socialize, and increase their intellectual development. Hearing impairment is a problem that can occur at any age and makes it difficult for someone to communicate verbally. Apart from this, hearing impairment can also result in delays in speech and language skills in children, which are also associated with difficulties in reading, writing, paying attention, and social interaction. Methods: The subjects of this research were children with hearing impairments. An experimental research design was used to determine the effect of certain treatments, with a one-group pre- and post-test design and a sample size of 30 people. bivariate test analysis with different tests to determine the effect of auditory perception training on improving the speaking ability of hearing-impaired children in Surakarta using the paired test technique. Results: The results of the analysis using the Wilcoxon rank test showed a statistical significance value of 0.000 (p ≤ 0.05), so there was a significant influence between auditory perception training and speaking ability in children with hearing impairment. Conclusion: The results of the study showed that the speaking ability of deaf children improved after auditory perception training was carried out. There is a significant effect of auditory perception training on the speaking ability of deaf children (p-value 0.000 < 0.05).